2008
DOI: 10.1177/0003319708327787
|View full text |Cite
|
Sign up to set email alerts
|

Relationship Between Noninvasively Measured Endothelial Function and Peripheral Arterial Disease

Abstract: Patients with PAD present endothelial dysfunction, but this does not seem to determine the severity of the disease.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
23
0

Year Published

2010
2010
2015
2015

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(24 citation statements)
references
References 35 publications
(64 reference statements)
1
23
0
Order By: Relevance
“…The higher pro-oxidative status of women is in line with the results of our previous study in which women had lower small artery elasticity index than men, and African-Americans had lower small artery elasticity indices than Caucasians. 19 The fact that higher endothelial cell ROS production of women was found in African-Americans but not in Caucasians suggests that African-American women represent a subgroup of patients with PAD who are particularly susceptible to progression of atherosclerosis, 34 and increased risk of coronary events. 34, 35 …”
Section: Discussionmentioning
confidence: 99%
“…The higher pro-oxidative status of women is in line with the results of our previous study in which women had lower small artery elasticity index than men, and African-Americans had lower small artery elasticity indices than Caucasians. 19 The fact that higher endothelial cell ROS production of women was found in African-Americans but not in Caucasians suggests that African-American women represent a subgroup of patients with PAD who are particularly susceptible to progression of atherosclerosis, 34 and increased risk of coronary events. 34, 35 …”
Section: Discussionmentioning
confidence: 99%
“…15, 17, 2123 We 24 and others 21 have found that endothelial function is impaired in PAD subjects. Furthermore, co-morbid conditions and cardiovascular risk factors are highly prevalent in subjects with PAD, such as metabolic syndrome, 25 diabetes, 2, 3 hypertension, 2, 3 dyslipidemia, 2, 3 smoking, 2, 3 ambulatory dysfunction 7, 8 and low physical activity levels.…”
Section: Introductionmentioning
confidence: 88%
“…Endothelial dysfunction is an early marker of vascular dysfunction prior to the development of structural changes and clinical symptoms [1521], contributes to the progression of atherosclerosis [21], and increases the risk of coronary events [15, 17, 2123]. We [24] and others [21] have found that endothelial function, as measured by the criterion method of brachial artery flow-mediated dilation, is impaired in PAD subjects.…”
Section: Introductionmentioning
confidence: 99%
“…We [24] and others [21] have found that endothelial function, as measured by the criterion method of brachial artery flow-mediated dilation, is impaired in PAD subjects. Apoptosis, cellular oxidative stress, and inflammation of the endothelium are factors that may contribute to the impaired endothelial function of subjects with PAD.…”
Section: Introductionmentioning
confidence: 99%